Gene Duplication Analysis Reveals No Ancient Whole Genome Duplication but Extensive Small-Scale Duplications during Genome Evolution and Adaptation of Schistosoma mansoni - Wang, Shuai; Zhu, Xing-quan; Cai, Xuepeng (Frontiers in Cellular and Infection Microbiology, 2017)
Gene duplication (GD), thought to facilitate evolutionary innovation and adaptation, has been studied in many phylogenetic lineages. However, it remains poorly investigated in trematodes, a medically important parasite group that has been evolutionarily specialized during long-term host-parasite interaction. In this study, we conducted a genome-wide study of GD modes and contributions in Schistosoma mansoni, a pathogen causing human schistosomiasis. We combined several lines of evidence provided by duplicate age distributions, genomic sequence similarity, depth-of-coverage and gene synteny to identify the dominant drivers that contribute to the origins of new genes in this parasite. The gene divergences following duplication events (gene structure, expression and function retention) were also analyzed. Our results reveal that the genome lacks whole genome duplication (WGD) in a long evolutionary time and has few large segmental duplications, but is extensively shaped by the continuous small-scale gene duplications (SSGDs) (i.e., dispersed, tandem and proximal GDs) that may be derived from (retro-) transposition and unequal crossing over. Additionally, our study shows that the genes generated by tandem duplications have the smallest divergence during the evolution. Finally, we demonstrate that SSGDs, especially the tandem duplications, greatly contribute to the expansions of some preferentially retained pathogenesis-associated gene families that are associated with the parasite's survival during infection. This study is the first to systematically summarize the landscape of GDs in trematodes and provides new insights of adaptations to parasitism linked to GD events for these parasites.